Effects of high concentrations of crude glycerin on blood biochemical profile of feedlot finishing lambs - van Cleef, E. H.C.B.; Almeida, M. T.C.; Silva, D. A.V.; Perez, H. L.; Paschoaloto, J. R. [UNESP]; Filho, E.S. Castro [UNESP]; Carvalho, V. B. [UNESP]; van Cleef, F. O.S.; Nociti, R. P. [UNESP]; Patiño, R. M.; Ezequiel, J. M.B. [UNESP] (FapUNIFESP (SciELO), 2023)
The objective of this study was to evaluate changes in the biochemical parameters of feedlot lambs fed with high concentrations of crude glycerin (GC). Forty crossbred lambs (Dorper × Santa Inês), noncastrated, weighing 21.7±2.7kg and 90 days old, were randomly assigned to four treatments (0, 10, 20, and 30% GC in the diet). To evaluate the biochemical parameters, blood samples (pre-prandial and 4 h after morning feeding) were collected on the first day and the day before slaughter, in each treatment. The high-density lipoprotein was linearly decreased (P<0.0001) when GC concentrations were increased in the diet. Alkaline phosphatase was quadratically affected by treatments (P=0.05), with greater values observed in blood from animals fed intermediate concentrations of CG, and gamma-glutamyl transferase was linearly increased (P=0.008). The blood urea was quadratically affected by treatments with lower values observed in blood from animals fed intermediate concentrations of CG. In conclusion, the replacement of up to 30% (based on dry matter) of corn grain by crude glycerin, in diets for feedlot finishing lambs, does not compromise the health status of these animals.
[Efeitos de altas concentrações de glicerina bruta no perfil bioquímico sanguíneo de cordeiros terminados em confinamento]
Keywords: Blood; by-product; coprodutos; glicerol; glycerol; ovinos; sangue; sheep